Feasibility of tofu as an alternative for traditional beef patties - Aguilar, Andrei Nicanor L., Cali, Mohammad Jebrin A., Cruz, Charles Julian B., Magpayo, Willander C., Miralles, Jose Marlou M., Rafael, Aeron D. C., Sese, Hennessy Rein L., Talisay, Trisha Jocel A. 4 0 16; 5
u
Feasibility Study: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2